KORELASI KECEMASAN DENGAN TENSION TYPE HEADACHE PADA MAHASISWA FAKULTAS KEDOKTERAN - I Made Mahardika Yasa,* I Putu Eka Widyadharma,* I Made Oka Adnyana* (Neurona Majalah Kedokteran Neuro Sains, 2016)
INTRODUCTION KNOWN TO ITS HIGH ACADEMIC LOAD MEDICAL COLLAGE TENDS TO PUT STUDENTS IN A HIGH STRESS LEVELS THIS CONDITION IS OFTEN REPORTED AS THE REASON FOR THE HIGH PREVALENCE OF ANXIETY AND TENSION TYPE HEADACHE TTH AMONG MEDICAL STUDENTS